The Morphogenesis of the Discourses of Religious Radicalism in Post-Authoritarian Indonesia - Yudha, Sakti Wira (Masyarakat: Jurnal Sosiologi, 2019)
The ambiguity of conception results in the explanation of the symptoms of religious radicalism at the global level becoming interpretative, depending on the contexts and meanings given by intellectuals. It becomes natural that knowledge of the conception overlaps with others, such as religious revivalism, fundamentalism, extremism, militancy, terrorism, and jihad. In line with the idea, knowledge on the discourses of religious radicalism in post-authoritarian Indonesia has been produced by institutions having the authorities and motives to make interpretations, according to the knowledge structure developed by their predecessors. These institutions, both state and civil society, construct the discourses of radicalism with descriptive explanations, to produce reproductive ideas rather than elaborative-transformative knowledge. The aforementioned opinion is true, but in practice, it is necessary to add a more comprehensive framework in explaining radicalism to anticipate its impacts. This article argues that the construction of knowledge on the discourses of radicalism must be placed within the framework of morphogenesis, where there are an elaboration and a transformation of the process of knowledge reproduction structurally, to produce a repertoire of new knowledge that is predictive. Mapping and construction of radicalism have been carried out based on products (results) as well as product makers (agencies) that form knowledge structures that can be used to mitigate as well as to provide early warning to control radicalism.